Desenvolvimento de um dispositivo para leitura da rede CAN veicular - Souza, Dionni Fernando Rodrigues de (2019)
In this work it was proposed the construction of a device that provides some information of a vehicle, such as rotation per minute, engine load, speed and temperature, from a study on the CAN protocol. The readings were made in a Wolksvagen Polo vehicle from the year 2018, for which an Eletronic Dev 1.0 development board was used which contained an MCP 2551 transceiver connected to the OBD2 of the vehicle, and a PIC controller, developing a code on the MPLAB platform, was possible to transmit and receive the data. The read data has been converted and transmitted via USB and displayed to an user on a computer and generated graphs of the same, for the correct analysis of the results.